Kelly, Kim. Photograph of Sheila and Bill Kelly at Clothilda O'Brien's. - Heritage NL
Kim Kelly provided a picture of Sheila and Bill Kelly at Clothilda O'Brien's. The two are sitting in a room, Sheila has on funny glasses and a hat and is speaking into a microphone.